Coffins of the brave : lake shipwrecks of the War of 1812 - Crisman, Kevin James, 1959- (Ed Rachal Foundation nautical archaeology series., 2014)
In Coffins of the Brave: Lake Shipwrecks of the War of 1812, archaeologist Kevin J. Crisman and his fellow contributors examine sixteen different examples of 1812-era naval and commercial shipbuilding. They range from four small prewar vessels to four 16- or 20-gun brigs, three warships of much greater size, a steamboat hull converted into an armed schooner, two gunboats, and two postwar schooners. Despite their differing degrees of preservation and archaeological study, each vessel reveals something about how its creators sought the best balance of strength, durability, capacity.